2022
DOI: 10.1111/1756-2171.12404
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning and market power after airline mergers

Abstract: We estimate a model of route-level competition between airlines who choose whether to offer nonstop or connecting service before setting prices. Airlines have full information about all quality, marginal cost, and fixed cost unobservables throughout the game, so that service choices will be selected on these residuals. We conduct merger simulations that allow for repositioning and account for the selection implied by the model and the data. Accounting for selection materially affects the predicted likelihood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…My model assumes that the outcomes from this period's choices are not realized until next period. 62 This method is similar to Li et al (2022) and Ho et al (2021). 63 This method is referred to as the block bootstrapping, which clusters standard errors at the market level.…”
Section: Structural Parametersmentioning
confidence: 85%
“…My model assumes that the outcomes from this period's choices are not realized until next period. 62 This method is similar to Li et al (2022) and Ho et al (2021). 63 This method is referred to as the block bootstrapping, which clusters standard errors at the market level.…”
Section: Structural Parametersmentioning
confidence: 85%
“…Empirical research on mergers and entry is hampered by selection: observed mergers are (presumably) both profitable and competitively benign. Recent applications address the issue by estimating structural models of competition-including the distribution of entry costs and fixed costs-exploiting observed entry and exit in the data (Li et al (2022); Ciliberto et al (2021); Fan and Yang (2021)). Post-merger equilibrium then can be computed allowing for entry or incumbent repositioning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al. (2019) estimate a model of route‐level airline competition and find that mergers increase the likelihood of product repositioning, as captured by a shift from connecting to non‐stop routes. Their key contribution is the development of a method that allows for selection on unobserved demand by conditioning on firms' pre‐merger choices.…”
Section: Introductionmentioning
confidence: 99%